2016
DOI: 10.1071/wf15037
|View full text |Cite
|
Sign up to set email alerts
|

Can pore-clogging by ash explain post-fire runoff?

Abstract: Ash plays an important role in controlling runoff and erosion processes after wildfire and has frequently been hypothesised to clog soil pores and reduce infiltration. Yet evidence for clogging is incomplete, as research has focussed on identifying the presence of ash in soil; the actual flow processes remain unknown. We conducted laboratory infiltration experiments coupled with microscope observations in pure sands, saturated hydraulic conductivity analysis, and interaction energy calculations, to test whethe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 78 publications
2
24
0
1
Order By: Relevance
“…Balfour et al () also concluded that the formation of an ash crust can potentially reduce erosion. In this experiment, it was possible to find an ash crust (see Figure ), and our data showed that it was highly permeable, as pointed out by Stoof et al ().…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Balfour et al () also concluded that the formation of an ash crust can potentially reduce erosion. In this experiment, it was possible to find an ash crust (see Figure ), and our data showed that it was highly permeable, as pointed out by Stoof et al ().…”
Section: Discussionsupporting
confidence: 82%
“…This ash‐preferential washing can be attributed to its lower particle size. Char particles contained comparatively more carbon content than white and grey ashes (Balfour, Doer, & Robichaud, ; Merino et al, ; Stoof et al, ), which resulted in a higher particle size, a stronger structure, were not likely to be compacted by raindrop, and, lately, increased surface roughness. Char particles would create more opportunities for runoff impoundment and sediment deposition than ashes (see Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings demonstrating the unlikeliness of an effect of pore clogging on infiltration in sandy soils (Stoof et al . , ) have shifted the research focus in the Rockies to the effects of differences between hydraulic conductivity of ash and underlying layers depending on texture, delayed water release from ash as a result of capillary forces, and lateral flow through ash and soil on top of a water repellent soil (Baker & Hillel, ; Bodí, Doerr, Cerdà, & Mataix‐Solera, ; Schroth, Istok, & Selker, ).…”
Section: Discussionmentioning
confidence: 99%
“…, ), especially not in sandy soil because ash and sand both have a negative surface charge (Stoof et al . , ).…”
Section: Wildfire Effects On Hydrological Processesmentioning
confidence: 97%
“…Larsen et al 2009). Stoof et al (2016) use laboratory experiments to explore whether this process does occur, but find that, at least for the sand used in their experiments, the presence of ash in the pores would be unlikely to promote enhanced overland flow. They discuss other mechanisms by which ash can affect post-fire hydrology, and present results demonstrating the important hydrological effect of ash on saturated hydraulic conductivity.…”
Section: Infiltrationmentioning
confidence: 99%